Strategi Guru dalam Proses Pembelajaran Praktik Mata Pelajaran Produktif di Sekolah Menengah Kejuruan - Aula Rizqiyana; Mohammad Fatkhurrokhman; Mustofa Abi Hamid (Departement of Mathematics Education, 2023)
This study aims to reveal the teacher's strategy in the learning process of practical productive subjects. The research was conducted at SMKN 1 Kramatwatu using a qualitative approach with a case study method. Data collection techniques through in-depth interviews, participant observation, and documentation. Determination of informants using snowball sampling technique. Informants in this study were teachers and students of class XI, the competence of Electrical Power Installation Engineering. The validity of the data in this study uses source, technique, and time triangulation. The data analysis technique used in this study is the interactive model Miles, Huberman and Saldana with the help of ATLAS TI 9 software. The results obtained in this study are (1) implementing contextual strategies used when conducting apperception activities and providing stimulus to students; (2) managing the class by implementing a rolling system, supervising and guiding students; (3) applying peer tutors; and (4) communicating persuasively by taking a personal approach to students and giving reprimands and advice when students violate or make mistakes.